Build an A-team play to their strengths and lead them up the learning curve - Johnson, Whitney (Harvard Business Review Press, 2018)
Do you want to have a high-performing team that strives for greatness, even in the face of uncertainty? Do you want to be a boss people love, while also driving high performance? Building morale and high performance are about engagement, and engagement is all about learning, argues Whitney Johnson. In over twenty years of research, investing, consulting, and coaching, Johnson has seen that people need continuous learning and fresh challenges to stay engaged. In this book you'll learn how to build an "A" team by leading team members on their current learning curve, how to design their jobs to maximize learning and engagement, and how to implement a seven-step process for advancing up the learning curve. We all want opportunities to learn, experiment, and grow in our jobs. The best bosses know this, and they know how to make it happen through thoughtful role design and just enough challenge. The result is a team that learns how to thrive, no matter what the industry throws at them.--
1805
Keywords: Organizational learning; Management; Employee morale; Employee motivation; Teams in the workplace; Engagement (Philosophy)